Potency of Trichoderma sp., antagonistic fungi derived from soil rhizospere, against two pathogens: Botryodiplodia theobromae Pat. and Fusarium sp. wilt in Vitro - Unun - Triasih (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
This study aims to to detennine the effectiveness of Trichoderma sp. as biocontrol agent through suitability test and test of its inhibition against pathogens Botryodiplodia theobromae Pat. and Fusarium sp. through antagonistic testing. Four Trichoderma sp. isolates: Trichoderma harzianum and Trichoderma viride from citrus plants, Trichoderma sp. from Manalagi apple plants, Trichoderma sp. from strawberry plants were tested against Fusarium sp. isolates and Botryodiplodia theobromae Pat. isolates. There are two treatments: suitability test of four Trichoderma sp. isolates and their inhibitory tests on Botryodiplodia theobromae Pat and Fusarium sp. Observations included presence or absence of inhibition zones, growth of pathogenic control pathways and pathogenic pathways in dual culture with antagonists. Test results showed that the four Trichoderma sp. isolatees did not show any inhibitory zones, which indicated that the tested antagonistic fungi were mutually compatible and could be combined. The best percentage of inhibition against pathogens Fusarium sp and Botryodiplodia theobromae Pat came from Trichoderma sp from strawberry plants by 84.62% and82.75%.